Determine the Rate of Harmful Maternal and Foetal Outcomes in Pregnant Adolescents - Shehla Parveen, Muntaha Hanif, Naheed Akhtar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this research is to examine whether or not adolescent pregnant women have adverse maternal and foetal outcomes. Study Design: Randomized controlled trial Place and Duration: The study was conducted at Gynaecology department of DHQ Teaching Hospital, Sargodha and DHQ Hospital Mianwali for duration of four months from August 2021 to November 2021. Material and Methods: In all, there were 84 participants in this research. Patients were between the ages of 14 and 45 years. After obtaining written agreement from patients, demographic data was collected. The patients were split into two groups, I and II, which were evenly distributed. Group I included 42 patients between the ages of 14 and 19, and Group II included 42 patients between the ages of 19 and over. Cesarean sections, instrumental deliveries, labour inductions and labour prolongations, hypertensive disorders, and other negative results were observed for the two cohorts. High rates of perinatal death and admission to the neonatal intensive care unit (NICU) were also found. SPSS 20.0 was used to analyse all of the data. Results: In group I mean age of the patients was 16.65±8.51 years and had mean BMI 20.05±6.33 Kg/m2 while in second group the mean age was 23.15±6.22 years and had mean BMI 24.7±9.51 Kg/m2. Study participants in adolescence (I) were more likely to have unfavourable foetal (perinatal death, low birth weight and low apgar score) and mother outcomes (C-section, Instrumental delivery, induction of labour, and prolonged labour) than those in the adult group (II). Conclusion: According to this research, premature neonatal critical care unit admissions and delayed intrauterine development are both on the increase. Pregnant teenagers are more likely to suffer from anaemia, a urinary tract infection, high blood pressure pregnancy, and a need for a surgical birth.